A new Inequity-in-Health Index based on Millenium Development Goals: methodology and validation - Eslava-Schmalbach, J.; Alfonso, Helman; Oliveros, H.; Gaitán, H.; Agudelo, C. (Elsevier, 2008)
Objectives: Developing a new Inequity-in-Health Index (IHI) assuming inequity as "inequality of health outcomes," based on Millennium Development Goals (MDG). Study Design and Setting: Ecological study. Countries from around the world were included from United Nations, the World Bank, and a nonprofit organization's databases. The reliability and validity of this bidimensional IHI was tested. Main factor analysis (promax rotation) and main component analysis were used. Results: Six variables were used for constructing the IHI was constructed with six variables: underweight children, child mortality, death from malaria in children aged 0-4, death from malaria at all ages, births attended by skilled health personnel, and immunization against measles. The IHI had high internal consistency (Cronbach's alpha = 0.8504), was reliable (Spearman > 0.9, P = 0.0000), and had 0.3033p around the world (range: 0p-0.5984p). IHI had high correlation with the human development and poverty indexes, health gap indicator, life expectancy at birth, probability of dying before 40 years of age, and Gini coefficients (Spearman > 0.7, P = 0.0000). IHI discriminated countries by income, region, indebtedness, and corruption level (Kruskal Wallis, P < 0.01). IHI had sensitivity to change (P = 0.0000). Conclusion: IHI is a bidimensional, valid and reliable index to monitor MDG. A new reliable methodology for developing bidimensional indicators is shown, which could be used for constructing other ones with their corresponding scores and graphs. © 2008 Elsevier Inc. All rights reserved.